Comparative Analysis of Lactobacillus gasseri and Lactobacillus crispatus Isolated From Human Urogenital and Gastrointestinal Tracts - Pan, Meichen; Hidalgo-Cantabrana, Claudio; Goh, Yong Jun; Sanozky-Dawes, Rosemary; Barrangou, Rodolphe (Frontiers in Microbiology, 2020)
Lactobacillus crispatus and Lactobacillus gasseri are two of the main Lactobacillus species found in the healthy vaginal microbiome and have also previously been identified and isolated from the human gastrointestinal (GI) tract. These two ecological niches are fundamentally different, notably with regards to the epithelial cell type, nutrient availability, environmental conditions, pH and microbiome composition. Given the dramatic differences between these two environments, we characterized strains within the same Lactobacillus species isolated from either the vaginal or intestinal tract to assess whether they are phenotypically and genetically different. We performed a series of comparative phenotypic assays including small intestinal juice and acid resistance, carbohydrate fermentation profiles, lactic acid production, and host interaction with intestinal Caco-2 and vaginal VK2 cell lines. We also developed a simulated vaginal fluid (SVF) to study bacterial growth in a proxy vaginal environment and conducted differential transcriptomic analysis between SVF and standard laboratory MRS medium. Overall, our results show that although strain-specific variation is observed, some phenotypic differences seem associated with the isolation source. We encourage future probiotic formulation to include isolation source and take into consideration genetic and phenotypic features for use at various body sites.